Satellite sectarianisation or plain old partisanship?: inciting violence in the Arab mainstream media - Watkins, Jessica (LSE Middle East Centre report, 2019)
This report assesses widespread claims that pan-Arab satellite news channels are responsible for inciting sectarian vio lence during the Arab uprisings. Based on an empirical study of how the most popular channels (Al-Jazeera Arabic and Al-Arabiya) and a competitive newcomer (Al-Mayadeen) have framed seminal events involving violence between sects in Syria and Iraq, the report finds that while often geo-politically charged, some of these claims are valid. While abusive language and direct promotion of vio lence are rare in a mainstream context, incitement to sectarian violence has been invoked primarily through linguistic and thematic tropes that forge legitimacy claims and narratives of victimhood. The paper draws on these findings to make recommendations for UK policymaker engagement with the Arab media.